Looking to Purpose: An Examination of Statutory Interpretation in Denaturalization Cases - A. Remi Balogun (Washington University Journal of Law & Policy, 2019)
This note analyzes the effects of recent decisions interpreting the Immigration and Naturalization Act (INA). The INA allows a naturalized citizen to be “denaturalized”, i.e. to have his or her citizenship revoked. This can happen where citizenship was “knowingly procured contrary to law.” Prior to the Supreme Court decision in Maslenjak v. United States, lower courts divided on whether a non-material misstatement in the citizenship application was a sufficient basis to denaturalize a citizen. In Maslenjak the Court determined a citizen could not be denaturalized unless the false statement could have justifiably resulted in the denial of naturalization. This note argues the Court came to the right conclusion but that contrary to the Court’s assertion the statutory text was ultimately ambiguous and the statutory purpose of the INA should have guided the decision.
Keywords: Denaturalization; Immigration; Citizenship; Statutory Interpretation; Immigration and Naturalization Act; INA